2006
DOI: 10.1038/sj.onc.1209416
|View full text |Cite
|
Sign up to set email alerts
|

Ganglioside GM3 promotes cell migration by regulating MAPK and c-Fos/AP-1

Abstract: Gangliosides have been proposed as modulators of transmembrane signaling. Recently, GM3, a glycosphingolipid containing monosaialic acids, is thought to be one of the key molecules of signal transduction in mammalian cells. In this study, we used mouse embryonic fibroblast cell lines (MEFs) established from sialyltransferase-I knockout mice (GM3 synthase KO mice) to evaluate the regulation of mitogenic signals by gangliosides. Cell proliferation assay revealed a higher growth potential of GM3 KO MEFs. Immunobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 46 publications
3
31
0
Order By: Relevance
“…This is consistent with the reciprocal result observed here; CAV1 deficiency reduces GM3 levels. Experiments in Siat9 / (GM3 synthase knock-out) MEFs demonstrated a reduction in GM3 directly correlated with increased cell motility and an up-regulation of the Ras/ Raf/MAP kinase pathway (Hashiramoto et al, 2006). Although it has been shown that different phospholipids differentially affect H-Ras and K-Ras (Kuroda et al, 1996), GM3 has been postulated as a key regulator for cellular signaling pathways, including those mediated by Ras proteins (Garofalo et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the reciprocal result observed here; CAV1 deficiency reduces GM3 levels. Experiments in Siat9 / (GM3 synthase knock-out) MEFs demonstrated a reduction in GM3 directly correlated with increased cell motility and an up-regulation of the Ras/ Raf/MAP kinase pathway (Hashiramoto et al, 2006). Although it has been shown that different phospholipids differentially affect H-Ras and K-Ras (Kuroda et al, 1996), GM3 has been postulated as a key regulator for cellular signaling pathways, including those mediated by Ras proteins (Garofalo et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Increased GSL biosynthesis (59,60) and GSL-mediated promotion of angiogenesis and metastatic tumor growth (6) have been demonstrated in different types of cancers. We have shown that GM3 is the predominant polar GSL produced by both myeloma cell lines and primary myeloma cells from patients with MM.…”
Section: Discussionmentioning
confidence: 99%
“…Signaling through lipid raft-associated GSLs has been shown to be an important process in many cell types, including myeloid cells, lymphocytes, and osteoclasts (OCs) (4). For example, GM3 has been shown to regulate lipid raft-mediated cell signaling and cellular adhesion in human lymphocytes (5)(6)(7). Increased synthesis of GM3 is also a defining characteristic that marks the differentiation and maturation of myeloid lineage precursors into monocytes and macrophages, a process that can be promoted by addition of GM3 (8).…”
Section: Introductionmentioning
confidence: 99%
“…in modulation of membrane-bound enzymes and ion-channels, cell-adhesion, neuritogenesis and membrane stability (Hakomori, 2003;Hashiramoto et al, 2006;Ledeen and Wu, 2006;Salazar et al, 2004;Sohn et al, 2006;Susuki et al, 2007;Wu et al, 2007;Yates and Rampersaud, 1998). Furthermore, anti-ganglioside autoimmunity and ganglioside turnover deficits cause neurological disorders (Ang et al, 2004;Maegawa et al, 2006;Simpson et al, 2004;Willison and Yuki, 2002).…”
Section: Introductionmentioning
confidence: 99%